2010
DOI: 10.1111/j.1872-034x.2010.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis in Egyptian patients with liver cirrhosis: Role of methylenetetrahydrofolate reductase C677T gene mutation

Abstract: The TT genotype of MTHFR is associated with an increased risk of PVT in Egyptian cirrhotic patients. Hyperhomocysteinemia could be considered as a relatively new risk factor for PVT in cirrhotic patients and plasma homocysteine should be investigated particularly in patients with PVT of unexplained etiology. The important clinical implication is that the readily available therapy of folate, vitamin B6 and B12 supplementation may reduce homocysteine and prevent further thrombotic complications in cirrhotic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
12
1
2
Order By: Relevance
“…Similar to a previous study , we found an association between HHcy and the severity of cirrhosis, as there was a significant correlation between the serum levels of Hcy and the MELD and Child–Pugh scores (Fig. a,b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to a previous study , we found an association between HHcy and the severity of cirrhosis, as there was a significant correlation between the serum levels of Hcy and the MELD and Child–Pugh scores (Fig. a,b).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown increased levels of homocysteine (Hcy) in patients with cirrhosis . Homocysteine is a thiol‐containing amino acid formed as a by‐product of transmethylation reactions.…”
mentioning
confidence: 99%
“…Although several studies have evaluated the potential implication of inherited thrombophilic disorders in the development of PVT in patients with cirrhosis, the results are still not conclusive 10,13,15,18,[25][26][27][28][29][30][31] (Table 2). Only 3 studies were prospective and longitudinal, 10,13,15 and although not all inherited factors were evaluated, no clear relationship between the studied inherited factors and development of PVT was found.…”
Section: Etiologymentioning
confidence: 99%
“…31 Thus, a total of 20 articles were finally included in our meta-analysis. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Among them, 12 articles were published in the full-text form, two in the letter form and six in the abstract form. All included studies were published in peer-reviewed journals between 2000 and 2012 (Table 1).…”
Section: Study Description and Qualitymentioning
confidence: 99%